Reading, Writing, and Rurality - Terri Suico (University of Oklahoma Libraries, 2024)
This review examines two recent scholarly books on teaching English language arts in rural areas. Robert Petrone and Allison Wynhoff Olsen's Teaching English in Rural Communities: Toward a Critical Rural English Pedagogy offers strategies and research-based rationales on how to teach students to think critically about depictions of rurality in texts. Teaching Diversity in Rural Schools by Lisa Hazlett focuses on using young adult literature to teach students in rural schools about diversity. The review evaluates the texts' contents and examines how both books contribute to educators' understanding of rurality and the specific needs of rural schools.